Influences of Buffer Size and Eb/No on Very Small Aperture Terminal (VSAT) Communictions - Debby Maureen Talumewo; Heru Sukoco; Fahren Bukhari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In data communication of the signal transmitted from the transmitter (Tx) to receiver (Rx) stations is very influential. Buffer and Eb/No are two parameters that influence the quality of signal. This research measures those parameters and the relationship among them. This research employs data collected on the Link STM-1 side in Makassar and Timika operated by PT. Telkom Metra Bogor. The period of data is carried out for 56 days taken by using Simple Management Network Protocol (SNMP). To analyze the relationship among those two parameters, we use product moment correlation (PMC) method. The result correlation of the data buffer and Eb/No with a level of real is 0.05 and then buffer set in modem CDM 700 is 50% with threshold Eb/No 12.1 dB and the modulations used 64-QAM. That resulted correlation of side in Makassar is 0.648 and the p-value is 0.000. Correlation of side in Timika is 0.722 and the p-value is 0.000. These results suggest that the two parameters are correlated strong and significant.